Improving Highest Security Lightweight block cipher (HISEC) Algorithm Using Key Dependent S-box - et.al, Warkaa Salim Najm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Information security is considered as a very critical issue in the transmission of information. Therforelossing or threatening the information transmission will therefore be a great loss in the process of transmitting the information. Recently, Lightweight block cipher Algorithms have gained wide acceptance and it is used in restricted applications, such as electronic passport, smart card, etc. In this study, a modified HISEC algorithm is proposed to enhance and improve the original HISEC algorithm by introducing the concept of a key dependent S-box. This proposal algorithm aims to generate a safer block of code and solve the problem of the fixed structure of the used S-box that was a vulnerability for the attacker. It was an impenetrable barrier facing the attacks of the (Linear cryptanalysis) and (Differential Cryptanalysis). The proposed algorithm showed some improvements when comparing it to the orginal algorithm.